Psychological assessment of ASD - Miller, Meghan (Henry Stewart Talks, 2020)
Overview of psychological assessment of ASD, Reasons for referral, Approaches to comprehensive assessment, General assessment administration guidelines, Key assessment domains include developmental/intellectual functioning, adaptive skills, academic functioning, and neuropsychological functioning, Comorbidity and differential diagnosis, Feedback to families